Dynamics of Moral and Ethical Development in Children through Religious-Based Education (Journal of Family Sciences, 2025)
In the contemporary world, as parents increasingly acknowledge the crucial role of quality education in shaping their children's future, particularly through religious education, uncertainties persist regarding the most effective platforms for its implementation and delivery. This qualitative research aims to explore optimal locations for imparting religious education to children and investigate its role in the moral and ethical development of children through faith-based learning. The research involved interviews with ten parent informants to gather insights into the best platforms and impacts of religious education on children's moral and ethical growth, which were then analyzed thematically to identify recurring patterns, key influences, and the extent of religious education's effectiveness in shaping children's character and ethical values. The findings show that religious education can be accessed through formal schooling, non-formal Quranic education, and the family. School-based religious education covers both theoretical and practical aspects, while Quranic education provides in-depth Islamic values. The family integrates religious values into daily life, with parents serving as primary educators and role models. The research highlights the significant impact of religious education on moral and ethical character, spiritual foundation, social skills, cognitive development, independence, and communication. It advocates for the integration of religious values across all educational platforms, emphasizing its role in fostering intellectually skilled and morally upright individuals.